Efficacy of pulverised leaves of Annona squamosa (L.), Moringa oleifera (Lam.) and Eucalyptus globulus (Labill.) against the stored grain pest, Tribolium castaneum (Herbst.) - Anita, S; Sujatha, P; Prabhudas, P (Recent Research in Science and Technology, 2012)
The pulverized leaves of Annona squamosa (L.), Moringa oleifera (Lam.) and Eucalyptus globulus (Labill.) were tested for their insecticidal and seed protective effect against the stored grain pest of wheat, Tribolium castaneum (Herbst). Different concentrations ranging from 0.05 to 2.0 g (0.05, 0.1, 0.15, 1.0 and 2.0 g) per 10.0 g wheat grains were tested against larvae and adults. When larvae were introduced to pulverized leaves of A. squamosa, M. oleifera and E. globulus separately, mortality rate increased with increase in concentrations and resulted in 100% mortality within a short period of eight, nine and ten days respectively with the highest concentration. The larvae which were introduced to these cultures did not grow well or molt to the next developmental stage. They have also shown very effective seed protection as the extent of damage produced in treated cultures were significantly reduced in comparison to control cultures. The seed protective effect ranged from 39% to 82% in A. squamosa, 34% to78% in M. oleifera and 42% to 88% in E. globulus. Considering the insecticidal and seed protective effect, these three plant powders could be employed as alternatives for chemical and synthetic pesticides at small scale level by farmers.